A ganar los espacios públicos (2010)
ABSTRACT: To Gain the Spaces Public". One of the important points in the scope of citizen security, and one of the props of the strategy of the citizen or democratic security, is that people occupy the streets. Nevertheless, there are urban and lacking infrastructure problems of planning of the cities, that attempt against this policy.